The Property Tax, an Essential Element of the Tax Collection in Centro, Tabasco - Calzada Falcón, Fernando (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
An example of a direct tax of progressive nature is the property tax.   In Mexico it is charged by the municipal government, which is one of the three types of governments. The municipal government is considered as the closest one to the needs of the population. This tax in Centro, Tabasco, as in most of the urban towns with a predominantly urban population, represents the main source of tax revenue and municipal revenue.   In this work, the following elements are analyzed:  the recent evolution of the property tax collection, its current behavior, its contribution to the municipal revenue, its contribution to the tax collection in all the 17 municipalities of the state, the statistics of the number of properties whose property tax payment is up to date, as well as the tax collection per property and how far the payment of this tax has improved through the digital platform.
Keywords: Public finances; Taxes; Municipality; Tax property; Tax collection.